PENGARUH MEDIA DOMINO PERKALIAN TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN MATEMATIKA KELAS 2 DI SDN MANDALA I - Siti Rofiqoh; M. Ridwan; Framz Hardiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study has grounded in the problem of student’s difficulties in learning of mathematics and the lacking of use of educational media. The goal of this exploration is to investigate the effectiveness of multiplication domino learning media effect the enhancement of critical thinking skills in 2 grade students in mathematics at SDN Mandala I, Rubaru District Sumenep Regency. This research is categorized as quantitative study that employs a numerical approach to test hypotheses and collect measurable and statically analyzable data with an experimental approach, utilizing a One Group Pretest-Posttest Design. The data collection methode applied by the researcher is total sampling that is 12 students.The findings of this research show that the multiplication domino learning media has an effect on enhnacing the critical thinking skills os 2 grade at SDN Mandala I, as seen from the the increasing value in the pretest score of 36.6 that given before the treatment, and the posttest scores of 71.6 given after given treatment.